2012
DOI: 10.4049/jimmunol.1103090
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Affects T Cell Responses through Modulation of CD46 Expression

Abstract: The ubiquitous protein CD46, a regulator of complement activity, promotes T cell activation and differentiation towards a regulatory Tr1-like phenotype. CD46-mediated differentiation pathway is defective in several chronic inflammatory diseases, underlying the importance of CD46 in controlling T cell function and the need to understand its regulatory mechanisms. Using an RNAi-based screening approach in primary T cells, we have identified that two members of the G-protein coupled receptor (GPCR) kinases were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
4
21
0
1
Order By: Relevance
“…Tumor necrosis factor (TNF) α, histamine, and proteases are immediately available upon degranulation and act to recruit neutrophils, T cells, and B cells (Galli & Tsai, 2012). Rapid de novo synthesis of leukotrienes and prostaglandins supports chemotaxis of various cell types and also influences antigen-presenting cell (APC) function and CD4 + T cell proliferation and differentiation (Boniface et al, 2009;Chen et al, 2009;Kickler et al, 2012;Krause et al, 2009;Yao et al, 2013). Cytokines produced by mast cells have the potential to significantly influence developing immune responses, with TNFα, IL-1, IL-4, IL-5, IL-6, IL-10, IL-12, and IL-13 all being capable of altering B and/or CD4 + T cell differentiation (Galli, Grimbaldeston, et al, 2008).…”
Section: Immunomodulatory Functions Of Mast Cellsmentioning
confidence: 99%
“…Tumor necrosis factor (TNF) α, histamine, and proteases are immediately available upon degranulation and act to recruit neutrophils, T cells, and B cells (Galli & Tsai, 2012). Rapid de novo synthesis of leukotrienes and prostaglandins supports chemotaxis of various cell types and also influences antigen-presenting cell (APC) function and CD4 + T cell proliferation and differentiation (Boniface et al, 2009;Chen et al, 2009;Kickler et al, 2012;Krause et al, 2009;Yao et al, 2013). Cytokines produced by mast cells have the potential to significantly influence developing immune responses, with TNFα, IL-1, IL-4, IL-5, IL-6, IL-10, IL-12, and IL-13 all being capable of altering B and/or CD4 + T cell differentiation (Galli, Grimbaldeston, et al, 2008).…”
Section: Immunomodulatory Functions Of Mast Cellsmentioning
confidence: 99%
“…A recent study demonstrated that CD46 activation induced EP4 expression and caused a decrease in the IL-10/IFN-g ratio in T cells, and that an EP4 antagonist reversed this effect on cytokine production after CD46 stimulation (Kickler et al, 2012). Nataraj et al (2001) showed mRNA expression of EP1, EP2, and EP4, but not EP3, on splenic T cells and B cells in mice.…”
Section: T Cellsmentioning
confidence: 99%
“…Tumor-derived COX2/PGE2 was shown to promote Foxp3 + Treg and Foxp3 - Tr1 cells in cancer (6367). In contrast, PGE2 inhibits the differentiation of non-tumor murine Foxp3 + Treg and of CD46-induced Tr1 cells (68, 69). …”
Section: Discussionmentioning
confidence: 99%